Effects of Antioxidants as Prestorage Seed Invigoration Treatments on Storability of Sunflower (Helianthus annuus L.) Seeds - YULLIANIDA YULLIANIDA; ENDANG MURNIATI (HAYATI Journal of Biosciences, 2005)
Oilly seeds, such as those of sunflower (Helianthus annuus L.), have short storability (3-4 months in room condition) due to oxidative stress during storage. The objective of this research was to determine whether prestorage seed invigoration by antioxidants, could improve storability of sunflower seeds. The research was performed using fresh harvested seeds. Prestorage seed invigorations were conducted by matriconditioning with water or antioxidants solution i.e. 4.17% curcumin or 100 and 150 ppm ascorbic acid. The seeds were stored for four months at room condition (28-29 oC and 62-79% relative humidity). Observations were conducted monthly. Experiment was arranged in split plot design. The result showed that all prestorage seed invigoration treatments were not effective to enhance storability of sunflower seeds compared to control. Inefficiency exogenous antioxidants was probably due to highly endogenous antioxidants activity during storage. This was indicated by the slow deterioration rate of control seeds, or due to high concentration of curcumin which was actually potential to enhance storability of sunflower seeds. It is suggested that presowing treatment and midstorage treatment will enhance storability of sunflower seeds.Back